2016
DOI: 10.3847/0004-637x/831/1/11
|View full text |Cite
|
Sign up to set email alerts
|

THE AGE AND DISTANCE OF THE KEPLER OPEN CLUSTER NGC 6811 FROM AN ECLIPSING BINARY, TURNOFF STAR PULSATION, AND GIANT ASTEROSEISMOLOGY

Abstract: We present the analysis of an eccentric, partially eclipsing long-period (P = 19.23 d) binary system KIC 9777062 that contains main sequence stars near the turnoff of the intermediate age open cluster NGC 6811. The primary is a metal-lined Am star with a possible convective blueshift to its radial velocities, and one star (probably the secondary) is likely to be a γ Dor pulsator. The component masses are 1.603 ± 0.006(stat.)±0.016(sys.) and 1.419 ± 0.003 ± 0.008M , and the radii are 1.744 ± 0.004 ± 0.002 and 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 134 publications
8
37
0
Order By: Relevance
“…While there is some tension between the age solutions for the two EB components, most of the data support an age for the cluster of 1 ± 0.05 Gyr (Sandquist et al 2016), in agreement with the Janes et al (2013) U BV RI photometric analysis. Sandquist et al (2016) also summarized the spectroscopic metallicity measurements in the literature from various sources, which agree on an approximately solar metallicity with values ranging from −0.02 to +0.04 dex. Finally, Sandquist et al (2016) found an interstellar reddening value of E(B−V ) = 0.07±0.02 (corresponding to A V = 0.22), while various literature values range from E(B − V ) = 0.05 to 0.14 (A V = 0.16 to 0.43).…”
Section: New Rotators In Ngc 6811supporting
confidence: 84%
“…While there is some tension between the age solutions for the two EB components, most of the data support an age for the cluster of 1 ± 0.05 Gyr (Sandquist et al 2016), in agreement with the Janes et al (2013) U BV RI photometric analysis. Sandquist et al (2016) also summarized the spectroscopic metallicity measurements in the literature from various sources, which agree on an approximately solar metallicity with values ranging from −0.02 to +0.04 dex. Finally, Sandquist et al (2016) found an interstellar reddening value of E(B−V ) = 0.07±0.02 (corresponding to A V = 0.22), while various literature values range from E(B − V ) = 0.05 to 0.14 (A V = 0.16 to 0.43).…”
Section: New Rotators In Ngc 6811supporting
confidence: 84%
“…NGC 6811 is also a solar-metallicity cluster and it is the youngest in the sample. For this we have three targets, all confirmed members (Sandquist et al 2016). All targets, except the NGC 188 target, is confirmed by asteroseismology to be in the helium-core-burning phase (Corsaro et al 2012;Stello et al 2016;Arentoft et al 2017).…”
Section: Targets Observations and Data Reductionmentioning
confidence: 99%
“…Prior to Campaign 13, Frandsen & Arentoft (1998), Arentoft et al (2005) and Andersen et al (2009) identified 23 main sequence pulsating variables in the field of NGC 1817. The age of NGC 1817 is such that the cluster turnoff falls completely in the instability strip, similar to NGC 6811 in the main Kepler field (Sandquist et al 2016). As a result, pulsating variables are among the brightest stars in the cluster, and their oscillation spectra may reveal information about the internal changes that result from their evolution away from the main sequence.…”
Section: Pulsating Stars In the Instability Stripmentioning
confidence: 83%